2004
DOI: 10.1016/j.clnu.2004.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Virgin olive oil reduces blood pressure in hypertensive elderly subjects

Abstract: Dietary VOO proved to be helpful in reducing the systolic pressure of treated HT elderly subjects. However, a greater resistance to the lowering effect of VOO of total and LDL-cholesterol and a greater susceptibility to TG oxidation was detected in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 72 publications
0
63
0
6
Order By: Relevance
“…24 Olive oil contains a high amount of oleic acid and is reported to decrease blood pressure in humans. [25][26][27] Here we show that the attenuation of hypertension after TTA treatment is accompanied by increased levels of oleic acid and its metabolites palmitoleic acid and icosatrienoic acid, probably because of increased ⌬9 desaturase activity. 28 An elevated level of palmitic acid 9 and a reduced level of stearic acid 8 in serum cholesteryl esters are associated with higher risk of hypertension; however, in the present study, no change was seen in the serum levels of these fatty acids.…”
Section: Gudbrandsen Et Al Prevention Of Renal Hypertension 463mentioning
confidence: 59%
“…24 Olive oil contains a high amount of oleic acid and is reported to decrease blood pressure in humans. [25][26][27] Here we show that the attenuation of hypertension after TTA treatment is accompanied by increased levels of oleic acid and its metabolites palmitoleic acid and icosatrienoic acid, probably because of increased ⌬9 desaturase activity. 28 An elevated level of palmitic acid 9 and a reduced level of stearic acid 8 in serum cholesteryl esters are associated with higher risk of hypertension; however, in the present study, no change was seen in the serum levels of these fatty acids.…”
Section: Gudbrandsen Et Al Prevention Of Renal Hypertension 463mentioning
confidence: 59%
“…Recruitment of inflammatory cells into the kidney starts with their interaction with selectins found on endothelial cells, which were reduced with a Mediterranean diet in a controlled study in humans (31). Inflammatory biomarkers, lipid profile, and BP have all been favorably affected by a Mediterranean diet (as a whole or its components) in several randomized trials, which may also translate into beneficial kidney effects (32,(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…showed that a diet enriched with 60 g of virgin olive oil, compared with 60 g of sunflower oil, daily for 4 weeks, reduced systolic but not diastolic BP in a group of 31 hypertensives, with no effect on 31 normotensive individuals 35 . In the same way, fish oil but not olive oil was effective in the reduction of diastolic BP in a crossover study on 10 hypertensive subjects (9 g fish oil or 9 g olive oil daily for 6 weeks) 27 .…”
Section: Feeding Trialsmentioning
confidence: 98%